Mabogo Percy More as a philosopher of emancipation - Shaw, Devin Zane (South African journal of philosophy, 2025)
In this essay, I read Mabogo More's work as a philosophy of emancipation, which I define as an approach to philosophy that aims to contribute to struggles for liberation. I show that there are numerous similarities between his work and Simone de Beauvoir's thought as set out in The Ethics of Ambiguity. I argue that both of them critique mainstream philosophy's so-called neutralism. I then reconstruct More's argument that Sartre's concept of contingency contributes to antiracist discourse and practice. I conclude by arguing that More's concept of contingency also subverts the claim, made by practitioners of the Western philosophical tradition, that the problems it considers are necessary and endogenous to that tradition - a claim that has been used to preclude a radical critique of this tradition from the approaches that it excludes.